2003
DOI: 10.1182/blood-2002-12-3917
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated cord blood transplantation for adult patients with advanced myelodysplastic syndrome

Abstract: We report the results of unrelated cord blood transplantation (CBT) for 13 adult patients with advanced myelodysplastic syndrome (MDS). The median age was 40 years, the median weight was 51 kg, and the median number of infused nucleated cells was 2.43 ؋ 10 7 /kg. Twelve patients had myeloid reconstitution, and the median time to more than 0.5 ؋ 10 9 /L (5 ؋ 10 8 /L) absolute neutrophil count was 22.5 days. A self-sustained platelet count more than 50 ؋ 10 9 /L was achieved in 11 patients at a median time of 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
4
45
0
1
Order By: Relevance
“…17,26 Here, we report an International survey of patients who received UCBT for MDS or sAML. DFS was 30%, which appears to be comparable to DFS after HSCT using other types of donors in large multicentric studies in high-risk MDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…17,26 Here, we report an International survey of patients who received UCBT for MDS or sAML. DFS was 30%, which appears to be comparable to DFS after HSCT using other types of donors in large multicentric studies in high-risk MDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 The Eurocord group reported the results from 16 adult patients with myelodysplastic syndrome who received CBT after myeloablative conditioning. 11 DFS at 2 years was 25%.…”
Section: Myelodysplastic Syndromementioning
confidence: 99%
“…As a result of the early successes with pediatric cord blood transplantation (CBT), cord blood from unrelated donors has been increasingly used as an alternative stem cell source for adult patients with hematological malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recently several reviews including the clinical results of adult CBT have been published. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this review, we focus on recent results of myeloablative CBT in adults.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study from Japan using MA UCB for 13 adult patients with advanced MDS showed a 2-year DFS of 76.2%. 75 Three patients relapsed and one patient had engraftment failure. Ten patients are alive with no evidence of disease at days þ 171 to 1558.…”
Section: Umbilical Cord Blood Transplantationmentioning
confidence: 99%